Mechanisms of life-course socioeconomic inequalities in adult systemic inflammation: Findings from two cohort studies. (January 2020) - Carmeli, Cristian; Steen, Johan; Petrovic, Dusan; Lepage, Benoît; Delpierre, Cyrille; Kelly-Irving, Michelle; Bochud, Murielle; Kivimäki, Mika; Vineis, Paolo; Stringhini, Silvia
Abstract: Disadvantaged socioeconomic conditions in childhood heighten systemic inflammatory levels in adulthood; however, life-course mechanisms underlying this association are largely unknown. In the present observational study, we investigated the roles of adulthood socioeconomic and lifestyle factors in mediating this association. Participants were from two prospective Swiss population-based cohorts (N = 5, 152, mean age 60 years). We estimated the total effect of paternal occupational position on adult heightened systemic inflammatory levels (C-reactive protein>3 mg/L), and the indirect effects via adulthood socioeconomic positions (SEPs: education and occupational position), financial hardship, and lifestyle factors (body mass index, smoking status, physical inactivity, and alcohol consumption). We estimated odds ratio (OR) and proportion mediated using counterfactual-based mediation models. Individuals whose father had a low occupational position had an OR of 1.51 [95% confidence interval (CI): 1.25, 1.84] for heightened inflammation compared to their more advantaged counterparts. This was jointly mediated (33 [95% CI: 14, 69]%) by adulthood SEPs, whereby the pathway through education followed by occupational position mediated 30 [95% CI: 11, 64]%, while the pathway via occupational position only mediated 3 [95% CI: 4, 13]%. Individuals with the lowest life-course SEPs had an OR of 2.27 [95% CI: 1.71, 2.98] for heightened inflammation compared to having the highest life-course SEPs. This was jointly mediated (63 [95% CI: 44, 97]%) by financial hardship and lifestyle factors. Our study supports a cumulative effect of life-course SEPs on adult heightened systemic inflammation along the pathway paternal occupational position -> education -> adult occupational position. Financial hardship and lifestyle factors in adulthood mediate half of that effect. Highlights: SEP experienced in childhood increases adult CRP levels. We study life-course mechanisms with path-specific counterfactual-based mediation. Childhood SEP operates via education followed by occupational position. Disadvantaged life-course SEPs increase adult CRP levels cumulatively. Targeting financial hardship and unhealthy lifestyle reduces the cumulative effect.